PUPPET ANIMATED BY ACTOR IN THE FUNCTION OF ACQUIRING OF THE INITIAL MATHEMATICAL CONCEPTS - Milovanović, Ana (Metodička teorija i praksa, 2025)
The subject of the paper is a research of the puppet animated by actor in the function of acquiring of the initial mathematical concepts. The research sample was the children puppet program of Television of Belgrade. Descriptive and prescriptive methods, as well as the content analysis technique were used. The paper confirmed the hypothesis that puppets can be successfully applied in the function of acquiring basic mathematical concepts. The research revealed a new aspect of the application of puppets, as an active performer in the presentation of basic mathematical concepts. The paper presents the best examples of puppet scenario, scenography and puppet mise-en-scène in which the potentials and specifics of puppet in the acquisition of basic mathematical concepts were most expressed. Their use as models in an institutionalized VOR is proposed.
Keywords: puppet animated by actor; initial mathematical concepts; art of puppetry; preschool child; institutionalized VOR